Keragaan Karakter Agronomi dan Sifat Tanak Sorgum Putih Lokal KD4 pada Komposisi Media Tanam yang Berbeda - Lizza Fauziah Suroya; Fitri Audia; Zanuba Fitroh Aulia; Gina Pebrianti; Salwa Febriyanti (Yayasan Literasi Sains Indonesia, 2025)
Sorghum (Sorghum bicolor (L.) Moench) is a strategic cereal crop for food diversification and food security due to its nutritional advantages and high adaptability to drought. Although white sorghum varieties are ideal for human consumption, they generally have lower levels of functional compounds such as tannins compared to colored sorghum varieties. Therefore, this study aims to evaluate the response of local sorghum to raw cocopeat media stress as a biofortification method to increase tannin content (moderate target of 1–3%) and analyze seed quality as a strategic effort to improve functional food potential. This study was conducted in two stages: field testing using a Completely Randomized Design (CRD) with four levels of planting media (100% soil; soil and husk 50:50%; soil and cocopeat 50:50%; soil, husk, and cocopeat 50:25:25%) to evaluate the agronomic characteristics of local sorghum KD4 against cocopeat stress and in the laboratory for soil characterization. Soil property characterization of sorghum was performed by iodine staining (Lugol) on the pollen and endosperm of sorghum seeds, where color changes observed under a light microscope would indicate waxy, nonwaxy, or heterowaxy properties. Modification of the growing medium significantly affects the potential yield characteristics of sorghum. The cocopeat treatment (P2) has the potential to be the best growing medium composition for biofortification because it is able to maintain seed yield even when there are indications of stress, while P3 causes a drastic decrease in yield. Additionally, KD4 sorghum consistently exhibits nonwaxy texture properties, supported by genotype and phenotype testing, indicating that this variety is suitable for food processing with a soft texture.